The relationship one-hour glycemia level at oral glucose tolerance test and non-alcoholic fatty liver disease (Annals of Medical Research, 2021)
None
Keywords: One-Hour Glucose Levels; Oral Glucose Tolerans Test; Non-Alcoholic Fatty Liver Disease; Hepatic Function Test.